Student Self-assessment in Regard to the Learning Outcome Achievement Level When Using the CDIO Approach at University of Information Technology - Vietnam National University, Ho Chi Minh City (Journal of Contemporary Educational Policies and Practices, 2022)
In 2010, Vietnam National University Ho Chi Minh City implemented the application of the CDIO (Conceiving - Designing - Implementing - Operating) approach, which has improved the quality of training in science and engineering majors. Nearly all of the curricula of Vietnam National University Ho Chi Minh City’s member schools are built completely or partially based on CDIO principles. The CDIO approach is well-suited to the practical context of Vietnamese technology training, which is adapted to the Vietnam National Qualification Framework and domestic as well as international quality accreditation criteria. CDIO-based programs focus on learners' competency upon the completion of a program. A quantitative study was conducted to analyze student self-assessment concerning achievements in their learning outcomes, and to determine the correlation between their performance and how well they fulfilled learning outcomes requirements. The data was collected from a random sample of 502 students at University of Information Technology - Vietnam National University Ho Chi Minh City. The results indicated that student self-assessments of learning outcomes are similar to their assigned grades, which means there was a positive correlation in the evaluation. In addition, results acquired from the Analysis of variance (ANOVA) revealed that there is a significant variation in the assessments of learning outcomes between majors from different faculties (5 items out of 17 items.) The findings are meaningful to lecturers, students and managers in improving learning, teaching and evaluation activities, which in turn help students improve their performance and prepare them for their future careers.
Keywords: Self-assessment; learning outcome achievement; CDIO approach; University of Information Technology